Permanent Learning: Continuing Your Teacher Education - Suyarova Mavjuda Ergashevna (Researchparks Publishing, 2022)
This article outlines goals for career growth teaching and the experiential learning cycle, the importance of feedback, types of feedback, self-assessment of a lesson, research for English language teachers, ideas for moving forward, professional associations and organizations, professional journals and teacher’s portfolios.